APLIKASI ANALITYCHAL HIERARCHY PROCESS (AHP) DALAM PENENTUAN ALTERNATIF PENGELOLAAN LINGKUNGAN INDUSTRI KOMPONEN ALAT BERAT BERBASIS PARTISIPASI DAN KEMITRAAN MASYARAKAT - Budi Setyo Utomo; Syamsul Maarif; Surjono Hadi Sutjahjo; Sumardjo Sumardjo (Graduate School Bogor Agricultural University (SPs IPB), 2011)
As a company engaged in the industrial sector by producing certain components and localized in an industrial area, there will be an impact on the environment. These impacts can be positive in the form of employment, reducing dependence on imported heavy equipment, increase in foreign exchange due to reduced imports and increased exports, increased government revenue from taxes, public facilities improvement and supporting infrastructure, and opening up opportunities for other related industries. These impacts can also be negative in the form of environmental degradation such as noise disturbance, dust, and micro climate change, and changes in social and cultural conditions surrounding the industry. This research was conducted to support increasing effectiveness and efficiency of corporate management, by determining alternative forms of managing the heavy industrial equipment components environment (PLIKAB)-based on participation and society partnerships. The determination of alternative uses analytical hierarchy process (AHP) with the help of the Criterium Decision Plus v3.04 software. These results indicate that according of experts, the environmental management of industrial waste heavy equipment components must consider the technological aspects of its management. This can be seen from the weighting of each element that indicates the technology element has the greatest weight, which is 0.456. Besides that, elements of human resources is also quite important (weight 0.289) as the manager and the supporting policies (0.140) as a boost to management regulations. Aspect Capital (0.075) and marketing (0.042) is currently not perceived as barriers. While the most influential actor in the management is the company (0.451), other stakeholders have enough role is the community (0.234). Jababeka (0.211) and cooperative business (0.104) has a smaller role in the management. The purpose element in relative management has a weight that is relatively balanced with elements of revenue (0.336) is the primary consideration in determining management strategies, although it should not ignore the aim of maintaining environmental quality (0.299), the purpose of minimizing conflict (0.194), and the purpose of increasing competitiveness (0.170). The best alternative for the management of industrial waste components of the heavy equipment is to form managers based on partnerships by different stock ownership (0.791). It is considered much better than by forming managers based on partnerships by the same stock (0.209). Key words : heavy equipment industry, management, environment, analitycal hierarchy process (AHP)